Rice Whitefly (Aleurocybotus occiduus Maria), a new emerging threat of rice production and its natural control in Chitwan, Nepal - Pokhrel, S; Thapa, RB (Agronomy Journal of Nepal, 2013)
An intensive field study was carried out to identify the problem causing reddish yellowing of the rice plants, access potential natural control of the suspected pests, estimate yield losses and to suggest an immediate, environmentally safe, possible control measures. Whitefly (Aleurocybotus occiduus Maria) was outbreak on main season rice in Chitwan valley, which affected a total of 20561 ha (Severly 177.3 ha, medium 2787.6 ha, low 6945.4 ha and mild 10691.7 ha) land, losing 9448 mt rice yield in 2003. Use of monoculture, susceptible varieties (Sabitri) and improper cultural operations, excess use of agrochemicals and unconsciousness on the population build up of pest and natural enemies were the causes of outbreak. A maximum of 1000 Whitefly nymphs /tiller were counted. Parasitoid, Encarsia sp was fond most functional natural enemy in the field. However, the population build up of the parasitoid was observed quite late. Rice plants recovered in some extent after heading when the Whiteflies were found naturally controlled. Higher the population of Whitefly proportionally decreased the tillers number/hill, fertile tillers/hill, grain weight/panicle and the grain yield/ha. Rice plants infested with high population of Whitefly (898/tiller) failed to gave rice yield, where medium population (335 / tiller) gave 1287 kg and low population (103 Whitefly/tiller) gave 3456.0 kg (30.8% less than of last year) /ha. Kanchhi Mansuli (4200 kg/ha) and Mansuli (3960 kgs/ha) were comparative tolerant varieties than the Sabitri. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7521 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.56-74